Association of social support with negative emotions among Chinese adolescents during Omicron-related lockdown of Shenzhen City: The roles of rumination and sleep quality - Guo, Tianyou; Zhang, Zhihao; Taylor, Alyx; Hall, Daniel L.; Yeung, Albert S.; Kramer, Arthur F.; Zou, Liye (Frontiers in Psychiatry, 2022)
Objective: Adolescents are likely to suffer from negative emotions such as depression and anxiety due to the rapid development of biological, cognitive and social changes. According to previous studies, possible protective factors for depression and anxiety include social support, rumination, and sleep quality among this age group. The present study first investigated association between social support and negative emotions during the Outbreak of Omicron variant, on this basis, to further determine the mediating role of rumination and sleep quality on this link. Method: A total of 1065 Chinese college students (51.5% female, Mage=13.80, SD=1.20) completed a psychosocial battery, including the Social Support Rating Scale (SSRS), the Pittsburgh sleep quality index (PSQI), the Ruminative Responses Scale (RRS), the Depression Anxiety Stress Scale (DASS). Serial multiple mediation analysis was conducted using PROCESS macro based on SPSS. Results: Social support, rumination, and sleep quality were significantly negatively correlated with negative emotional states (Ps<.05). Further, rumination and sleep quality were found partially mediated the relationship between social support and negative emotional states. Conclusions: For early detection and prevention of depression and anxiety, cognitive behavioral interventions for rumination and sleep quality are necessary for adolescents with low social support.